Wearable Assistive Robotics and Its Interaction with Muscular Recruitment Strategies - Sierotowicz, Marek; Brusamento, Donato; Missiroli, Francesco; Bornmann, Jonas; Gonzalez-Vargas, Jose; Masia, Lorenzo; Castellini, Claudio (Springer Science and Business Media Deutschland GmbH, 2025)
Understanding the interaction between wearable robotics and muscular recruitment is crucial for efficient workload sharing. This paper examines previous experiments involving three assistive technologies: a tendon-driven glove, a compliant exoskeleton for overhead work, and a functional electrical stimulation prototype. The findings highlight the importance of transparent control interfaces and biomechanical optimization in enhancing the usability and effectiveness of wearable assistive devices.
CRIS-Team Scopus Importer:2025-03-28